Orogenital ulcers and the Behcet’s disease - Nagabhushanarao, Bhavana V.; Narmada, Vatti; Nageswararao, Boddapati; Kumar, Kolavennu S. (International Journal of Research in Medical Sciences, 2024)
Behcet’s’s disease is a systemic vasculitis involving small to large veins and arteries. It is a sporadic disease, mostly prevalent among the ancestors of the silk route. It is characterized by recurrent oral ulcers, genital ulcers, and uveitis. It also can manifest as skin, vascular, gastrointestinal, neurological, cardiac, and renal involvement. Though overall mortality is around 5%, delay in diagnosis and treatment may lead to significant morbidity. Cardiovascular and pulmonary arterial aneurysms are dreadful complications of this disease. Being uncommon in south India it is liable to be wrongly diagnosed and treated. Delay in the diagnosis and treatment may lead to severe complications. Here we present a case of Behcet’s disease which was managed at primary health care inadequately. We also demonstrated a quick response to steroids which are the mainstay of treatment. In this case presentation we illustrated pre and post treatment scrotal and oral Behcet’s’s lesions for clinicians to memorize. We also discussed international criteria to diagnose Behcet’s disease (ICBD) in concurrence with our case. In this presentation, we briefly described the involvement of other systems and their treatment. This article also elaborated on the latest developments in the treatment of Behcet’s disease.